Voids characteristics of asphaltic concrete containing coconut shell - Abdullah, M.E. (Institute of Physics Publishing, 2017)
Asphalt durability is often linked to the thickness of the asphalt coating on the aggregate particles. In order to have adequate film thickness in asphaltic concrete, there must be sufficient space between the aggregate particles in the compacted pavement. This void space is referred to as voids in total mix (VTM), voids with filled bitumen (VFB), and voids in mineral aggregate (VMA). Hence, this study investigates the performance of coconut shell (CS) as coarse aggregate replacement on voids characteristics of asphaltic concrete. Four CS were used as coarse aggregates replacement in asphalt mixture namely 0, 10, 20, 30, and 40 (by weight volume). The voids properties of asphalt mixture were determined based on Marshall Mix design test. Test results show that VTM and VMA values were decrease with the increasing bitumen content where VFB was increase with increasing bitumen content. Furthermore, increasing the percentage of coconut shell in asphalt mixture was found to increases the voids value up to a peak level and then decreases with further additions of CS. © Published under licence by IOP Publishing Ltd.